2012
DOI: 10.1111/j.1365-2494.2012.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inoculants and wilting on silage fermentation and nutritive characteristics of red clover–grass mixtures

Abstract: Various management practices (e.g. wilting, application of silage additives or adding a grass component) can be used to improve silage fermentation of pure red clover (Trifolium pratense L.). Therefore, the aim of this laboratory ensiling study was to investigate the effects of varying proportions of red clover and perennial ryegrass (100/0, 66/33, 33/66, 0/100) on silage quality during two consecutive years. In addition, two wilting levels [target dry matter (DM): 300 vs. 400 g kg−1] in combination with lacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…A few studies have demonstrated that formic acid decreased NH 3 -N concentration in silage (Nagel and Broderick 1992;Ding et al 2013;Li et al 2016). The application of LP alone, or in combination with AD, significantly increased LA content in alfalfa-corn mixed silage, which coincides with Krawutschke et al (2013).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…A few studies have demonstrated that formic acid decreased NH 3 -N concentration in silage (Nagel and Broderick 1992;Ding et al 2013;Li et al 2016). The application of LP alone, or in combination with AD, significantly increased LA content in alfalfa-corn mixed silage, which coincides with Krawutschke et al (2013).…”
Section: Discussionsupporting
confidence: 80%
“…A few studies have demonstrated that formic acid decreased NH 3 -N concentration in silage (Nagel and Broderick 1992;Ding et al 2013;Li et al 2016). The application of LP alone, or in combination with AD, significantly increased LA content in alfalfa-corn mixed silage, which coincides with Krawutschke et al (2013). As can be seen from Table 3, the alfalfa-corn ratio factor had a significant effect on the nutritive value of mixed silage, which agrees with Zhang et al (2015), because the differences on nutrition indexes between alfalfa and corn were obvious (Table 1) and different mixture ratios led to this remarkable influence.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations